Alternative use of the cough drug - N-acetylcysteine in psychiatry: a review of recent clinical trials - Cieszkowska, Joanna; Czubala, Marta; Czerwik, Julia; Dmochowska, Joanna (Journal of Education, Health and Sport, 2024)
Introduction and purpose N-acetylcysteine (NAC) is one of the more popular drugs, widely available in pharmacies, used to treat wet cough. NAC’s diverse mechanism of action has drawn the attention of researchers for its great potential in the treatment of many conditions. Indeed, it has been noted that administration of NAC allows indirect modulation of the central nervous system, which may be important in the treatment of psychiatric diseases. The following review focuses on recent reports of NAC’s potentially beneficial effects on psychiatric conditions such as depression, schizophrenia, obsessive-compulsive disorder, and addiction. Description of the state of knowledge Based on studies conducted on animals (rats), a positive effect of NAC has been proven, observing a reduction in the severity of depressive symptoms. Based on the above data, more and more human studies are being conducted, where the effect of NAC on the symptoms of various mental conditions is being investigated. In recent years, the antioxidant, anti-inflammatory and neurotransmitter function modulating effects of NAC on the brain have been proven, with significant potential in the treatment of mental illness. Conclusions The potential impact of NAC on the treatment of mental illness is a rapidly developing topic in recent years. On the basis of available scientific data, partial reduction of symptoms of mental illnesses through the use of NAC has been confirmed. It is a very promising drug, which in this indication requires additional studies to unequivocally confirm its beneficial effects on the functioning of the central nervous system.